'All the World's a Stage': William Shakespeare's Cultural Capital 400 Years after his Death. Issue 1 (2nd January 2017) - Muñoz-Valdivieso, Sofía
Abstract: The article reviews the evolution of Shakespeare studies over the last 50 years and proposes a narrative to trace its development since the commemoration of Shakespeare's birth in 1964 in three phases: first, the unfolding from the 1970s to the 1990s of what I have called the postmodern paradigm in Shakespeare studies, which I argue breaks with previous humanist universalising readings of his plays; second, the serious consideration of Shakespeare on screen in the 1990s and the 2000s, an academic field that grows in the context of performance and popular culture studies; and, third, the scholarly analysis of Shakespeare's plays in the digital media in the new millennium, a period that also witnesses the study of the bard on the global stage of world cultures, with the continued perception that his work is both core British heritage and inevitable global commodity. These most recent trends in Shakespeare studies were present in the overall approach to the celebration of the bard during the 2012 London Cultural Olympiad, an event with Shakespeare at its centre that can be seen as the forerunner of the explosion of activities in 2016 for the 400th commemoration of his death.